Exergoeconomic perspective to evaluate and optimize supercritical carbon dioxide coal-fired power generation system. (15th September 2021) - Chen, Dongxu; Han, Zhonghe; Guo, Dongyang; Bai, Yaping; Zhao, Linfei
Highlights: The exergoeconomic model suitable for SCO2 coal-fired system is established. The cost formation process of system is revealed. The exergoeconomic performances of components and system are evaluated. The effects of crucial parameters on performances of system are summarized. The selection criterion of operation parameters of system is proposed. Abstract: The application of supercritical carbon dioxide (SCO2 ) Brayton cycle to coal-fired power generation system has attracted increasing attention since 2018. In this study, the SCO2 coal-fired power generation system is evaluated and optimized from the exergoeconomic perspective. The purpose is to conduct comprehensive and in-depth analysis of this system. The simulated model of the studied system and corresponding exergoeconomic model are initially established. Subsequently, the cost formation process of system is revealed and the exergoeconomic performances of components and overall system are evaluated. The effects of five crucial operation parameters on exergoeconomic performance evaluation parameters are explored. Finally, the exergoeconomic performance of the studied system is optimized and compared with the preliminary design case. The results show that the unit exergy cost of coal, flue gas, SCO2, shaft work, and electricity are 4.705 $/GJ, 6.586 $/GJ, 9.329 $/GJ, 10.175 $/GJ, and 10.331 $/GJ respectively. Design changes should firstly be targeted to superheat cooling wall and high temperature recuperator due to its higher expense cost rate. Moreover, for the overall system, the exergy decrease cost rate is dominant and the total product unit cost is 15.988 $/GJ under preliminary design case. In parametric analysis, importantly, the method of increasing maximum operation temperature/pressure to reduce total product unit cost is limited. From exergoeconomic optimization results, for the system with high facility cost, a moderate decrease of maximum operation temperature/pressure can achieve the reduction of total product unit cost. The ultimate conclusion indicates that the selection criterion of operation parameters is to maintain the balance of exergy efficiency and total facility cost of the overall system. In conclusion, this study could provide reference to the construction of real SCO2 coal-fired power generation system.